Optimizing BTS Development in 3T Sulawesi via Telkomsel's Business Ecosystem Approach - Asyraf, Akhmad; Tricahyono, Dodie (Penerbit Goodwood, 2023)
Purpose: Communication services have become a primary need for Indonesian society, especially high-speed cellular data services, commonly known as broadband services through cellular networks. Accelerating the development of underdeveloped regions is mandated in Chapter IV of the Preamble to the 1945 Constitution of the Republic of Indonesia as part of the national aspiration to realize a sovereign, united, sovereign, just, and prosperous Unitary State of the Republic of Indonesia. On the other hand, telecommunications providers in rural areas, especially in 3T regions, face challenges, as the number of customers does not justify the investment costs, resulting in a burden on the company's investment and operations. This research aims to identify the actors involved, understand the interrelationships between them, and provide an overview of the current BTS development business model in 3T areas. Research methodology: Qualitative methods were used, including data collection through literature studies and in-depth interviews, utilizing an ecosystem mapping approach. Results: Using a business ecosystem approach, this research succeeded in identifying the actors and interactions between actors involved in BTS development in the 3T region, as well as producing ecosystem reconfiguration as a strategy for optimizing BTS development in the 3T region. Conclusions: The reconfiguration of the BTS development ecosystem in Indonesia’s 3T (frontier, outermost, and underdeveloped) areas highlights significant shifts in the roles and interactions among key actors, despite the absence of new stakeholders. The main actors experiencing changes in their roles and collaboration dynamics include Telkomsel, BAKTI (the government agency), PEMDA (local governments), and Fiberhome. Telkomsel’s roadmap outlines a structured approach through short-term, medium-term, and long-term planning phases, reinforcing its leadership in advancing telecommunications services in underserved regions. Limitations: However, the expansion of cellular networks through BTS construction is still uneven, especially in 3T areas (Frontier, Remote, and Underdeveloped). Contribution: This research provides recommendations for optimizing BTS development in 3T areas.